Game AI Pro 360. Guide to movement and pathfinding (CRC Press, 2020)
"Cutting-edge game AI movement and pathfinding techniques primarily from game developers of shipped commercial games. The book acts as a toolbox of techniques that can be applied to many common and not-so-common situations"--